Seasonal changes of jumping performance and knee muscle strength in under-19 women volleyball players - Rousanoglou, E. N.; Barzouka, K. G.; Boudolos, K. D. (The Journal of Strength and Conditioning Research, 2013)
The purpose of the study was to compare the seasonal changes (preparation period [PP] and competition period [CP]) of vertical jumping performance and knee muscle strength in a team of under-19 women volleyball players (N = 12, 16.2 ± 1.5 years). The countermovement jump was used to evaluate jumping performance. The isometric knee extension moment at 150 ms from the onset of contraction (T150) and at a maximum of contraction (TMAX) were determined at 9 knee angles (from 10° to 90°, full knee extension = 0°). The peak isokinetic knee extension (TISOK-EXT) and flexion (TISOK-FLEX) moment were determined at 60, 180, and 240°/s. Repeated-measures analysis of variance was applied to the differences between PP and CP (p < 0.05). Significant increases in jumping performance were found for jump height, peak impulse, total impulse, peak power, and takeoff velocity (p < 0.05). At the knee flexion angles from 40° to 90°, T150 was significantly increased (p < 0.05), whereas the increase was not significant at the rather extended knee angles of 10°, 20°, and 30° (p > 0.05). Only at 90° of knee flexion (p < 0.05), TMAX was significantly increased. With the exception of TISOK-FLEX at 60°·s-1 (p < 0.05), the increases of TISOK-EXT and TISOK-FLEX were not significant (p > 0.05). The TISOK-EXT/TISOK-FLEX ratios were not significantly changed (p > 0.05). The main application of the study is that it provides performance standards and potential criteria for variable selection for jumping performance and knee muscle strength seasonal evaluation.